Voluntary rate of torque development is impaired after a voluntary versus tetanic conditioning contraction. Issue 2 (12th October 2013) - Smith, Cameron B.; Allen, Matti D.; Rice, Charles L.
ABSTRACT Introduction: Both voluntary and evoked conditioning contractions will potentiate muscle twitch contractile properties. The response of a voluntary contraction to each condition type is not well understood but it may be a more functional model than evoked twitch potentiation. Methods: Baseline measurements from tibialis anterior included: maximal isometric twitch torque and rate of torque development (RTD); maximal evoked 50‐Hz torque; and maximal voluntary ballistic RTD. Potentiation was induced by a 10‐s voluntary or tetanic contraction (∽78% MVC), followed by 2 twitches and 2 ballistic contractions. Results: Twitch properties (torque and RTD) were potentiated equally after each conditioning contraction. Ballistic RTD was greater post‐tetanus (390.2 ± 59.3 Nm/s) than post‐voluntary (356.4 ± 69.1 Nm/s), but both were reduced from baseline (422.0 ± 88.9 Nm/s). Conclusions: Twitch potentiation was similar between conditioning contraction types, but ballistic RTD was lower after post‐tetanus than post‐voluntary. The results indicate central inhibition or fatigue concurrent with peripheral potentiation. Muscle Nerve49: 218–224, 2014